2018
DOI: 10.30595/lks.v12i1.2197
|View full text |Cite
|
Sign up to set email alerts
|

A Linguistic Landscape in Purwokerto: Power and Solidarity Stand Strong in a Culinary Center

Abstract: This paper is about the existence of linguistics landscape along the Soeharso’s street Purwokerto which shows the diverse people in using language of their stores, restaurants, eateries, cafes, or street vendor banner whereby traders use their own prominent language in monolingualism, bilingualism, or multilingualism. For restaurants, eateries, or street vendors, they include person’s name as their stall name, and also include the origin of the food pioneer to show their sense of solidarity, while shops, distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The recent research study findings are similar to the previous studies done by Pamuji and Khristianto (2018) and . Both studies found that Indonesian, English, and Javanese are the most frequently used in a culinary signs.…”
Section: Preserving Traditional Heritagesupporting
confidence: 91%
See 2 more Smart Citations
“…The recent research study findings are similar to the previous studies done by Pamuji and Khristianto (2018) and . Both studies found that Indonesian, English, and Javanese are the most frequently used in a culinary signs.…”
Section: Preserving Traditional Heritagesupporting
confidence: 91%
“…Many studies of linguistics landscape have been published around the world; some of them are conducted in Istanbul (Inal et al, 2020), Botswana (Akindele, 2011), Japan (Bayne, 2018), Italy (Vermeulen, 2019), Los Angeles (Chun, 2014), Canada (Dressler, 2015), Texas (Hult, 2014), Singapore (Tang, 2018), Philadelphia (Leung and Wu, 2012), and Philippines (Ellaga and Valdez, 2020) and Indonesia (Andriyanti, However, despite a large body of research on linguistics landscape in the last ten years, the extensive researches on linguistics landscape have thus far centered mostly on certain aspects like education ( Sayer, 2010;Rowland, 2013;Andriyanti, 2019;Sinaga et al, 2020), literacy practice (Leung & Wu, 2012, Poveda, 2012; bilingualism (Hulf, 2014, Dressler, 2015; multilingualism (Gorter, 2013); tourism spot (Widiyanto, 2019;Nirmala, 2019;Solikhah et al, 2020;da Silva et al, 2021), Urban planning ( Malinowski, 2016); and public services (Purnanto and Ardhian, 2020; Ardhian et al, 2021) to mention but a few. So far the researchers have concerned, the linguistics landscape related to culinary in Indonesia has been studied by several researchers (Pamuji and Khristianto, 2018;. For example, Pamuji and Khristianto (2018) investigated the linguistics landscape of the culinary center along Jalan Soeharto which has become one of the city's destinations in Purwokerto.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on linguistic landscapes in similar environment have been done by some researchers (Pamuji & Khristianto, 2018;Firdausiyah, 2019;Lestari, 2019;Manan et al, 2014;Shang and Gou, 2017). The first three focusing on the sites in Indonesia, meanwhile the other two have their exploration in Malaysia and Singapore.…”
mentioning
confidence: 99%
“…Shang and Gou (2017) took the shop signs, just like Lestari (2019) who has gone deeper by shooting out the spaces in a mall. Meanwhile, Pamuji and Khristianto (2018) specify their data on culinary shops in a commercial complex, by collecting data from the passerby perspective. Despite of a big gap between their settings, a similar result seems to be conclusive that English is the dominant code in such an area, emphasizing that it is the best language for selling products.…”
mentioning
confidence: 99%